2021
DOI: 10.3390/e23030303
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Entropy Measurement Principle of Propositional Formulas in Conjunctive Normal Form

Abstract: The satisfiability (SAT) problem is a core problem in computer science. Existing studies have shown that most industrial SAT instances can be effectively solved by modern SAT solvers while random SAT instances cannot. It is believed that the structural characteristics of different SAT formula classes are the reasons behind this difference. In this paper, we study the structural properties of propositional formulas in conjunctive normal form (CNF) by the principle of structural entropy of formulas. First, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In local search, an initial solution (starting point), which lies near a high-quality one, may cost significantly less steps (flips) to achieve that satisfactory solution. In our previous works [ 39 , 40 ], we confirmed that a variable’s structural entropy significantly influences the probability that it will be flipped later in local search. Based on this result, we developed strategies for initiating solutions and such strategies greatly improve two state-of-the-art solvers, and .…”
Section: Initiating a Solution Based On Variables’ Structural Entropysupporting
confidence: 77%
See 1 more Smart Citation
“…In local search, an initial solution (starting point), which lies near a high-quality one, may cost significantly less steps (flips) to achieve that satisfactory solution. In our previous works [ 39 , 40 ], we confirmed that a variable’s structural entropy significantly influences the probability that it will be flipped later in local search. Based on this result, we developed strategies for initiating solutions and such strategies greatly improve two state-of-the-art solvers, and .…”
Section: Initiating a Solution Based On Variables’ Structural Entropysupporting
confidence: 77%
“…The motivation of VSEI is as follows. The smaller a variable’s structural entropy is, the more stable its truth value is, hence the smaller the probability that it will be flipped later [ 40 ]. That is, a variable with smaller structural entropy should probably be assigned earlier, compared to those variables with greater ones.…”
Section: Initiating a Solution Based On Variables’ Structural Entropymentioning
confidence: 99%
“…Since Shannon introduced the theory of information entropy in 1948 [ 36 ], it has been widely used in complexity measurement [ 37 , 38 , 39 , 40 , 41 ]. Entropy is also used to quantitatively describe the uncertainty and order degree of system structure, which can facilitate complexity evaluation [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%